Childbearing Across Partnerships in Australia, the United States, Norway, and Sweden. - Thomson, Elizabeth; Lappegård, Trude; Carlson, Marcia; Evans, Ann; Gray, Edith (Demography (Springer Nature), 2014)
This article compares mothers' experience of having children with more than one partner in two liberal welfare regimes (the United States and Australia) and two social democratic regimes (Sweden and Norway). We use survey-based union and birth histories in Australia and the United States and data from national population registers in Norway and Sweden to estimate the likelihood of experiencing childbearing across partnerships at any point in the childbearing career. We find that births with new partners constitute a substantial proportion of all births in each country we study. Despite quite different arrangements for social welfare, the determinants of childbearing across partnerships are very similar. Women who had their first birth at a very young age or who are less well-educated are most likely to have children with different partners. The educational gradient in childbearing across partnerships is also consistently negative across countries, particularly in contrast to educational gradients in childbearing with the same partner. The risk of childbearing across partnerships increased dramatically in all countries from the 1980s to the 2000s, and educational differences also increased, again, in both liberal and social democratic welfare regimes.